Sediment Suspension Distribution Models in East Canal Flood Estuary Waters, Semarang, Central Java, Indonesia - Alyssa Hutasuhut; Aris Ismanto; Baskoro Rochaddi; Lilik Maslukah; Rikha Widiaratih (Tecno Scientifica Publishing, 2022)
The study was carried out in Semarang City, Central Java, Indonesia, along the East Canal Flood River. There are several community activities that produce some pollutants and total suspended solids (TSS) was one of the elements is. The river transports these pollutants to the estuary. These coastal regions provide exceptional life support for creatures. This study attempts to determine the concentration value of suspended solids, its suitability to the pollution threshold value, and the distribution pattern of the sediment suspension based on hydrodynamic parameters, using the Delft3D program. This study estimated the distribution of sediment suspensions by not only describing conditions at a single point in time, but also representing seasonal conditions periodically. The concentration ranges between 0.04 kg/m3 and 0.06 kg/m3, making it good for aquaculture, marine tourism, and conservation. At high tide, the dispersion of suspended sediment leads to the land; at low tide, it leads to the sea. This study can be utilized as a supplement to prior research, which mainly consisted simply of sediment suspension distribution maps.